This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: 18.01 Calculus Jason Starr Fall 2005 Lecture 4. September 15, 2005 Homework. No new problems. Practice Problems. Course Reader: 1F1, 1F6, 1F7, 1F8. 1. Product rule example. For u = 3 x + 1, what is u ( x )? Since u u = 3 x + 1, ( u u ) = (3 x + 1) = 3. By the product rule, ( u u ) = u u = 2 uu . Thus solving, u + u u ( x ) = 3 / (2 u ) = x 1 / 2 / 2 . 3(3 + 1) 2. The derivative of u n . From above, ( u 2 ) equals 2 uu . By a similar computation, ( u 3 ) equals 3 u 2 u . This suggests a pattern, d ( u n ) n 1 du = nu . dx dx 18.01 Calculus Jason Starr Fall 2005 This can be proved by induction on n . For n = 1 , 2 and 3, it was checked. Let n be a particular integer (for instance, 70119209472933054321). For that integer, suppose the result is known, d ( u n ) n 1 du = nu . dx dx The goal is to prove the result for n + 1, that is, n +1 ) d ( u du = ( n + 1) u n ....
View
Full
Document
This note was uploaded on 06/03/2008 for the course MATH B6A taught by Professor Moretti during the Spring '08 term at Bakersfield College.
 Spring '08
 Moretti
 Chain Rule, Implicit Differentiation, Product Rule

Click to edit the document details